Study on Clinicopathologic Correlation of Malignant Tumors of Urinary Bladder - Badruddoza, SM; Azim, FA; Rahman, AJEN; Kamal, M; Barua, AR; Khan, KH; Chowdhury, T (TAJ: Journal of Teachers Association, 2011)
A total of 57 cases clinically suspicious to be urinary bladder malignancies were studied for clinico-histopathological correlations. Patients had different age ranges, sexes, occupations and habit of smoking but all of them presented with painless gross or microscopic haematuria. Histopathological examinations revealed all as malignant tumors of different types and grades. Gross male smokers preponderance and significant proportion of cases from age range 50 to 80 years were noted. So in a proper clinical setting, every haematuria case should be evaluated specially for bladder malignancy. DOI: http://dx.doi.org/10.3329/taj.v14i2.8392 TAJ 2001; 14(2): 81-84